Citraan dalam Novel Asmaraloka Karya Arata Kim - Aldika, Zaldi; Rahayu, Sri (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This study examines the use of imagery in the novel "Asmaraloka" by Arata Kim, highlighting the magical creativity of literature that enriches the reader's experience. Using a qualitative approach and descriptive method, the research identifies, classifies, analyzes, and concludes imagery of sight, hearing, movement, touch, and smell in the novel. The findings reveal various imagery employed by the author to enrich the narrative. The implications of this research in education include the development of literature teaching in high school, while theoretically contributing to understanding the use of imagery in literary works. Practically, this research can be used as teaching material in literature subjects, enriching the learning experience of Indonesian language and literature.